Decolonising globalised curriculum landscapes: The identity and agency of academics. (18th August 2021) - Reyes, Vicente; Clancy, Sharon; Koge, Henry; Richardson, Kevin; Taylor, Phil
Abstract : page_1 other This article explores how academics in a higher education institution (HEI) make sense of the challenges that they encounter in a neoliberal context typified by an increasingly globalised curriculum landscape. Two key questions are explored: What are the contours of the shifting boundaries which define the 'global curriculum' in HEI contexts? How do academics navigate and make sense of this fluidity in an uncertain and disputed landscape? Using reflections on practice emanating from the redesign of educational courses to respond to a rapidly changing student cohort, this inquiry takes an auto-ethnographic approach, offering the perspectives of five academic staff from a UK-based HEI through the lens of their lived experiences, and acknowledging the emerging shifts in identities that they experience and the need to confront tensions in this curriculum space. We conclude that our own scrutiny of, and critical reflections on, our identity and positionality as teachers and education practitioners represent a form of decoloniality, enabling us to find ways to share what we know without excluding knowledge outside it and to welcome contributions and possibilities beyond our own experiences. In terms of how we should act, we recognise that it must be through a dialectic that does not seek cultural supremacy or sovereignty.